2017
DOI: 10.1097/ta.0000000000001440
|View full text |Cite
|
Sign up to set email alerts
|

The value of the injury severity score in pediatric trauma

Abstract: Background The Injury Severity Score (ISS) is the most commonly used injury scoring system in trauma research and benchmarking. An ISS>15 conventionally defines severe injury; however, no studies evaluate whether ISS performs similarly between adults and children. Our objective was to evaluate ISS and AIS to predict mortality and define optimal thresholds of severe injury in pediatric trauma. Methods Patients from the Pennsylvania trauma registry 2000–2013 were included. Children were defined as age<16years.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
83
3
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(99 citation statements)
references
References 25 publications
10
83
3
3
Order By: Relevance
“…One advantage of the Berlin Definition is that it uses the MAIS definitions, which in our study showed better agreement between experts than the ISS, which is consistent with Brown et al [ 24 ]. Consequently, ISS-based definitions might give better results by automatic estimation of the ISS, and perhaps to some extent the MAIS for the Berlin Definition, as is done in some registries.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…One advantage of the Berlin Definition is that it uses the MAIS definitions, which in our study showed better agreement between experts than the ISS, which is consistent with Brown et al [ 24 ]. Consequently, ISS-based definitions might give better results by automatic estimation of the ISS, and perhaps to some extent the MAIS for the Berlin Definition, as is done in some registries.…”
Section: Discussionsupporting
confidence: 91%
“…Another reason might be that the calculation of the ISS can be difficult. As an example of the discussion concerning the ideal cutoff if using the ISS to identify a patient with polytrauma, a recent registry study of nearly 400,000 patients showed that for children compared with adults, the optimal cutoff was ISS ≥25 points [ 24 ]. We cannot address this issue here, because there were few children included in our study, but it emphasizes the point that there is an ongoing need for discussion of the ISS ≥16 points cutoff value for defining polytrauma and of all ISS-based classification the interobserver reliability was best in ISS ≥25 points.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a lower HB level during admission was more common in the infants with TBI with poor neurologic outcomes compared to those with favorable neurologic outcomes. We also found that a lower HB was associated with poor neurologic outcomes and in-hospital mortality independent of other risk factors including initial GCS, ISS, RBCT, neurosurgery, imaging findings, and retinal hemorrhage, all of which have been reported to be strong predictors for outcomes in infants with TBI in previous studies 15,20,21 . Previous studies have reported that initial GCS and ISS are both risk factors for a poor prognosis in pediatric TBI cases 22,23 .…”
Section: Discussionsupporting
confidence: 68%
“…In addition, the nadir HB developed within the first 2 days, and was thus a feasible and www.nature.com/scientificreports www.nature.com/scientificreports/ practical parameter. In previous studies on pediatric TBI, initial GCS and ISS were the most commonly used risk factors for a poor prognosis [20][21][22][23] . In the final model of our study, we identified initial GCS and ratio of ΔHB as the predictors for a poor prognosis, both of which were more powerful than ISS.…”
Section: Discussionmentioning
confidence: 99%
“…Injury severity was assessed by the Injury Severity Score (ISS) which was considered as a continuous scale and categorized into mild (0-14), moderate (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29), and severe (30-75) trauma. [28][29][30] Arterial hypotension was defined as a systolic blood pressure of <60 mm Hg in neonates 0 to 30 days old, <70 mm Hg in infants 30 days to 1 year old, <70 mm Hg + (age in years x 2) mm Hg in children 1 year to 10 years old, and <90 mm Hg in children and adolescents > 10 years old based on reference points established in the Pediatric Advanced Life Support guidelines. 31 copyright.…”
Section: Study Variablesmentioning
confidence: 99%